Nicotinamide is an endogenous agonist for a C. elegans TRPV OSM-9 and OCR-4 channel - Awani Upadhyay (Nature Portfolio, 2016)
TRPV are cation channels activated by physical and chemical stimuli. Here the authors show that nicotinamide is a soluble, endogenous agonist for orthologous TRPV channels fromC. elegans and Drosophila, unveiling a metabolic-based regulation for TRPV channel activity.